A new genus of Scoliidae (Insecta: Hymenoptera) from the Lower Cretaceous of northeast China. (January 2015) - Zhang, Qi; Zhang, Haichun; Rasnitsyn, Alexandr P.; Jarzembowski, Edmund A.
Abstract: A new genus and species of Scoliidae (Hymenoptera), Sinoproscolia yangshuwanziensis gen. et sp. nov., is described from the Lower Cretaceous Yixian Formation in Inner Mongolia, China and attributed to the subfamily Proscoliinae. Some characteristics, including complete crossveins 1r-rs and 2r-m in the forewing, and a free section present in almost all longitudinal veins indicate a basal position of the new genus in Proscoliinae. The presence of vein 2A suggests its atavistic origin in Sinoproscolia gen. nov. rather than a true plesiomorphy.